Disrupted Idylls : Nature, Equality, and the Feminine in Sentimentalist Russian Women’s Writing (Mariia Pospelova, Mariia Bolotnikova, and Anna Naumova) – With translations by Emily Lygo - Stohler, Ursula (2016)
The study provides a close analysis of literary works by women in late-18<UP>th</UP>- and early-19<UP>th</UP>-century Russia, with a focus on Anna Naumova, Mariia Pospelova, and Mariia Bolotnikova. Political, social and feminist theories are applied to examine restrictions imposed on women. Women authors in particular were fettered by a culture of feminisation strongly influenced by the French philosopher Jean-Jacques Rousseau. As Sentimentalism and its aesthetics began to give way to Romantic ideals, some provincial Russian women writers saw an opportunity to claim social equality, and to challenge traditional concepts of authorship and a view of women as mute and passive.